The Introduction of the Soviet Passport Regime in the Lithuanian SSR in 1944–1953 - Laukaitytė, Regina (Teisė, 2018)
In 1944–1953 several campaigns of passport issuance were carried out in Lithuania: already in December 1944 the residents of Vilnius and Kaunas received Soviet type personal identity documents, in November 1945–March 1946 – all the residents of Lithuania. The article seeks to identify: 1) when, under what circumstances and what were the first documents issued in Lithuania; 2) how did the system of control over the population enabled by the passport regime function; 3) what is known about the spread of counterfeit documents.
Keywords: none